Clinical Use of Hydrogen Sulfide to Protect Against Intimal Hyperplasia - Macabrey, Diane; Longchamp, Alban; Déglise, Sébastien; Allagnat, Florent (Frontiers in Cardiovascular Medicine, 2022)
Arterial occlusive disease is the narrowing of the arteries via atherosclerotic plaque buildup. The major risk factors for arterial occlusive disease are age, high levels of cholesterol and triglycerides, diabetes, high blood pressure, and smoking. Arterial occlusive disease is the leading cause of death in Western countries. Patients who suffer from arterial occlusive disease develop peripheral arterial disease (PAD) when the narrowing affects limbs, stroke when the narrowing affects carotid arteries, and heart disease when the narrowing affects coronary arteries. When lifestyle interventions (exercise, diet…) fail, the only solution remains surgical endovascular and open revascularization. Unfortunately, these surgeries still suffer from high failure rates due to re-occlusive vascular wall adaptations, which is largely due to intimal hyperplasia (IH). IH develops in response to vessel injury, leading to inflammation, vascular smooth muscle cells dedifferentiation, migration, proliferation and secretion of extra-cellular matrix into the vessel’s innermost layer or intima. Re-occlusive IH lesions result in costly and complex recurrent end-organ ischemia, and often lead to loss of limb, brain function, or life. Despite decades of IH research, limited therapies are currently available. Hydrogen sulfide (H2S) is an endogenous gasotransmitter derived from cysteine metabolism. Although environmental exposure to exogenous high H2S is toxic, endogenous H2S has important vasorelaxant, cytoprotective and anti-inflammatory properties. Its vasculo-protective properties have attracted a remarkable amount of attention, especially its ability to inhibit IH. This review summarizes IH pathophysiology and treatment, and provides an overview of the potential clinical role of H2S to prevent IH and restenosis.